Longitudinal Associations of Driving Status and Occupational Dysfunction With Health Outcomes After Acquired Brain Injury - Shuto Takehara; Tasuku Sotokawa; Yuta Tauchi; Rie Sakamoto; Yoshihiro Kanata; Kazuhisa Domen (American Journal of Occupational Therapy, 2026)
Importance Driving facilitates community involvement after acquired brain injury (ABI). While driving cessation can lower quality of life, the long-term health impacts of driving resumption, and how baseline occupational dysfunction (OD) affects them remain unclear. Objective To investigate the longitudinal associations between driving status (resumption vs. cessation) and health outcomes following ABI and determine whether baseline OD influences these associations. Design Retrospective longitudinal cohort study using linear mixed-effects models for trajectory analysis. Setting Single inpatient and outpatient driving rehabilitation program at a Japanese medical center. Participants Sixty-two patients with ABI who completed driving assessments and follow up. Outcomes and Measures Physical component summary and mental component summary (MCS) scores from the eight-item short-form health survey, Zung self-rating depression scale (SDS) scores, and life-space assessment (LSA) scores, with the baseline classification and assessment of occupational dysfunction score as the primary moderator. Results Driving resumption was significantly associated with MCS (β = 6.409), SDS (β = −7.310), and LSA (β = 22.768) score improvements. These associations were most pronounced in patients with higher baseline OD (e.g., interaction β for MCS = 0.152, p < .01; interaction β for SDS = −0.149, p = .01). Conclusions and Relevance Driving resumption is associated with clinically meaningful improvements in mental health-related quality of life, depressive symptoms, and life space, particularly in patients with severe OD at baseline. These findings highlight the importance of assessing baseline OD during driving rehabilitation to understand better and support the long-term wellbeing and community participation of patients with ABI.